2022
DOI: 10.1136/jim-2021-002206
|View full text |Cite
|
Sign up to set email alerts
|

Review of existing evidence demonstrates that methotrexate does not cause liver fibrosis

Abstract: It has long been believed that methotrexate in therapeutic doses causes progressive liver injury resulting in advanced fibrosis and cirrhosis. Historically, this was a common indication for serial liver biopsy. However, new evidence suggests that methotrexate may not be a direct cause of liver injury; rather the injury and fibrosis attributed to methotrexate may be mediated by other mechanisms, specifically non-alcoholic fatty liver disease. The recent widespread use of non-invasive assessment of liver fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(57 reference statements)
2
2
0
1
Order By: Relevance
“…In fact, the latest evidence supported that the hepatic injury and brosis could be contributed by factors other than methotrexate 23,24 , as shown in our cohort such as DM, BMI and disease severity (PASI). The only novel biomarker that demonstrated a modest linear correlation with the cumulative dosage of methotrexate was serum ATX level.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In fact, the latest evidence supported that the hepatic injury and brosis could be contributed by factors other than methotrexate 23,24 , as shown in our cohort such as DM, BMI and disease severity (PASI). The only novel biomarker that demonstrated a modest linear correlation with the cumulative dosage of methotrexate was serum ATX level.…”
Section: Discussionsupporting
confidence: 82%
“…Based on our ndings, interval liver biopsy based on the cumulative dosage of MTX would not be recommended as its risk outweighed the bene t. TE is relatively inexpensive, non-invasive and could avoid the potential sampling error in liver biopsy. It has been proposed to replace liver biopsy for monitoring in those with non-alcoholic fatty liver disease (NAFLD) and could be applied widely in patients with PsO/PsA and RA 22,[24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…It binds to receptors present on the cell membranes, inhibiting the binding of toxins in these sites, reducing druginduced hepatocellular damage thus reduce the levels of (ALT,AST,ALP and TSB) in the liver. This outcomes was reported by [41][42] who was demonstrated that the membrane structure and integrity of the liver cells were preserved in Montelukast treated group which would otherwise have been destroyed by MTX Hepatic tissue in the control group had a normal morphological appearance according to histology. Significant histological abnormalities in the rats' livers of the MTX group included hepatocellular damage evidenced by hydropic degeneration, congestion of the central vein, dilatation of the sinusoid, inflammation, bile duct injury, and necrosis, which is consistent with [43] who discovered the same histopathological alterations that are in line with the numerous earlier studies of MTX-induced hepatotoxicity in rat models, in which the Methotrexate group displayed significant histological abnormalities, including hepatic cellular necrosis and an invasion of mononuclear cells, along with sinusoidal enlargement, mononuclear cell infiltration, and an increase in the number of kupffer cells of kupffer cells.…”
Section: The Effect Of Montelukast On Liver Function Test (Alt Ast Al...supporting
confidence: 65%
“…По данным РПКИ, в которое вошли пациенты с метаболическим синдромом, лечение МТ ассоциировалось с увеличением концентрации печеночных ферментов по сравнению с плацебо [109]. Однако лечение МТ не приводило к увеличению эластичности ткани печени (Фиброскан), а развитие гепатотоксичности не зависело от длительности приема и кумулятивной дозы МТ [116,117]. Факторами риска печеночной патологии были СД 2-го типа, а также, вероятно, регулярный прием НПВП.…”
Section: нежелательные реакции время развития рекомендацииunclassified